A semiclassical approximation for the nonstationary two-dimensional nonlinear Schrodinger equation with an external field in polar coordinates; Russian Physics Journal; Vol. 49, iss. 7 - Borisov A. V. Aleksey Vladimirovich (2006, 2006)
Title screen